PENGARUH SUPERVISI PENDIDIKAN TERHADAP PENINGKATAN PROFESIONALISME GURU - Jannah, Miftachul; Harris, Taufiq; Faizin, Ahmad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Teacher professionalism is a crucial element in determining the quality of education, requiring ongoing development through planned, systematic, and effective supervision activities. This study aims to comprehensively analyze the impact of educational supervision implementation on efforts to improve teacher professionalism in schools. The research method used was a literature review using a qualitative approach, by examining secondary data from various relevant academic sources over the past five years, involving school principals as supervisors and teachers as objects of supervision. Key stages of the study included library data collection, in-depth thematic analysis, and narrative synthesis of supervisory practices. Key findings indicate that educational supervision plays a significant role in optimizing aspects of planning, implementation, and evaluation of learning outcomes. Collaborative and reflective supervision has been proven to motivate teachers to develop pedagogical and professional competencies, and encourage the creation of learning innovations through the provision of constructive feedback. The main conclusion emphasizes that educational supervision is not merely an administrative oversight tool, but rather a continuous development process that is essential for improving the quality of teaching. Synergy between supervisors and teachers through a humanistic approach is the main key to realizing the professionalism of educators, which has an impact on improving the overall quality of national education. ABSTRAK Profesionalisme guru merupakan elemen krusial penentu mutu pendidikan yang memerlukan pembinaan berkelanjutan melalui kegiatan supervisi yang terencana, sistematis, serta efektif. Penelitian ini bertujuan untuk menganalisis secara komprehensif bagaimana pengaruh implementasi supervisi pendidikan terhadap upaya peningkatan profesionalisme guru di lingkungan sekolah. Metode penelitian yang diterapkan adalah studi literatur review menggunakan pendekatan kualitatif, dengan mengkaji data sekunder dari berbagai sumber akademik relevan dalam kurun waktu lima tahun terakhir yang melibatkan kepala sekolah sebagai supervisor dan guru sebagai objek supervisi. Tahapan penting penelitian mencakup pengumpulan data pustaka, analisis tematik mendalam, serta sintesis naratif mengenai praktik supervisi. Temuan utama menunjukkan bahwa supervisi pendidikan memiliki peran signifikan dalam mengoptimalkan aspek perencanaan, pelaksanaan, hingga evaluasi hasil pembelajaran. Supervisi yang dijalankan secara kolaboratif dan reflektif terbukti mampu memotivasi guru untuk mengembangkan kompetensi pedagogik maupun profesional, serta mendorong terciptanya inovasi pembelajaran melalui pemberian umpan balik yang konstruktif. Simpulan utama menegaskan bahwa supervisi pendidikan bukan sekadar alat pengawasan administratif semata, melainkan sebuah proses pembinaan berkelanjutan yang esensial untuk meningkatkan kualitas pengajaran. Sinergi antara supervisor dan guru melalui pendekatan yang humanis menjadi kunci utama dalam mewujudkan profesionalisme tenaga pendidik yang berdampak pada peningkatan mutu pendidikan nasional secara keseluruhan.